From Narcissism to Schizophrenia: The Subject and Method in Jean-Luc Marion, Emmanuel Levinas and Edmund Husserl - Pandya, Rashmika (My University, 2008)
This work explores three phenomenological views of subjectivity in light of methodological transitions within phenomenology since its inception. Jean-Luc Marion offers a critique of Husserl 's transcendental ego in Cartesian Questions. This critique characterizes Husserl's transcendental ego as a 'schizophrenic ego'. This criticism is aimed at phenomenology's intentionality thesis as well as the method of reduction(s). Marion is influenced by Emmanuel Levinas' ethics and takes issue with a 'theoretical bias' within Husserl 's thought, a bias that characterizes subjectivity in the same terms as objectivity. I frame Marion's and Levinas' views of subjectivity in terms of two seemingly opposed 'origins' of subjectivity: Marion's notion of subjectivity embraces a notion of an originally auto-affected subject, while Levinas' position privileges an originally hetero-affected subject. I argue that both these views of subjectivity remain within dualist perspectives. Both thinkers try to overturn a hierarchy of reason over sensation/ emotion/ feeling by calling for a radically passive institution of subjectivity through either a givenness prior to subjectivity (Marion) or the face to face encounter with an Other (Levinas). However, both positions end up instituting a new hierarchy, one where reason is subjugated to feeling. Rather than dismantling dualism both thinkers end up defending a revised hierarchical thinking. I argue that Husserl's transcendental ego is indeed a 'schizophrenic ego' (i.e., a split ego) in Marion's sense but that this is not a problem for classical phenomenology but an alternative to either an auto-affected subject or a hetero-affected subject. Husserl's works on internal time-consciousness and passive and active synthesis illustrate a necessary correlation between passivity/ activity, matter/ form, reason/ emotion, ego/ world and self/ other which moves beyond the hierarchical thinking associated with traditional dualist thought. Husserl's notions of correlation and synthesis actually suggest a subject that is always intentionally related to the world and others and is also intentionally self-related. The implicit aim of this work is to suggest an alternative to an ethics of irreducibility endorsed by both Marion and Levinas. Husserlian phenomenology offers the possibility of an ethics of reciprocity, which paradoxically does not undermine the irreducibility of the subject, others or the world.
Keywords: phenomenology; subjectivity; Jean-Luc Marion; Emmanuel Levinas; Edmund Husserl; schizophrenic ego; reciprocity; ethics